Islam Nusantara vs Progressive Islam: Dynamics and Transformation in the Modern Context of Indonesia - Syafrion, Syafrion; Asmaret, Desi; Lahmi, Ahmad (International Journal of Islamic Thought and Humanities, 2024)
This journal explores the comparative dynamics and transformative processes of Islam Nusantara and Progressive Islam within the modern Indonesian context. Islam Nusantara, rooted in local traditions and cultural syncretism, emphasizes moderation, tolerance, and integration with indigenous practices. In contrast, Progressive Islam focuses on rationalism, reform, and socio-political activism, drawing from contemporary interpretations of Islamic teachings. This study examines the historical evolution, theological foundations, and socio-political implications of both movements, highlighting their respective responses to global challenges and local contexts. By analyzing primary sources, field studies, and interviews with key figures, this research elucidates the complexities and intersections between these two paradigms. The findings reveal how Islam Nusantara and Progressive Islam shape Indonesian Muslim identity, influence public discourse, and contribute to the broader narrative of Islamic thought in the 21st century. This study provides a nuanced understanding of the ongoing negotiation between tradition and modernity in Indonesian Islam, offering insights into the future trajectories of these influential movements.